1988
DOI: 10.1111/j.1471-4159.1988.tb01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Cyclic AMP of Phorbol Ester‐Potentiated Norepinephrine Release from Guinea Pig Brain Cortical Synaptosomes

Abstract: The involvement of Ca2+/phospholipid-dependent protein kinase (protein kinase C, PKC) and cyclic AMP-dependent protein kinase in the K+-evoked release of norepinephrine (NE) was studied using guinea pig brain cortical synaptosomes preloaded with [3H]NE. 12-O-Tetradecanoylphorbol-13-acetate (TPA), a potent activator of PKC, enhanced the K+-evoked release of [3H]NE, in a concentration-dependent manner, but with no effect on the spontaneous outflow and uptake of [3H]NE in the synaptosomes. The apparent affinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…PKC activators and inhibitors had no effect on the spontaneous tritium overflow in agree ment with the results in other tissues (10,30,31,35,37), suggesting that PKC may be re sponsible for modulating rather than for mediating NE release from the canine saphe nous veins.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…PKC activators and inhibitors had no effect on the spontaneous tritium overflow in agree ment with the results in other tissues (10,30,31,35,37), suggesting that PKC may be re sponsible for modulating rather than for mediating NE release from the canine saphe nous veins.…”
Section: Discussionsupporting
confidence: 75%
“…PDBu also enhanced significantly the KCl-evoked tritium overflow in the presence of phentolamine, indicating that the enhancement caused by PDBu is not due to blockade of presynaptic a 2-adreno ceptors. Furthermore, it has been reported that inhibition of neuronal NE reuptake is not responsible for the phorbol ester-potentiated NE release (30,31). PKC activation causes blockade of K+ currents (23) or facilitation of Na+ (32) and Ca 2+ (33) currents, each of which results in an enhancement of NE re lease.…”
Section: Discussionmentioning
confidence: 99%
“…Since cAMP and phorbol esters have each been shown to modulate V-ATPase activity (32-34), studies were performed to examine the contribution of these two signaling pathways to the IL-1-induced increase in V-ATPase activity. Two specific inhibitors of cAMP-dependent PKA, H-89 (35) and KT5720 (36,37), markedly abrogated the increase in pH i recovery induced by IL-1 without affecting recovery rates in control cells (Fig. 5, A and B, respectively).…”
Section: Effect Of Il-1 Involves Camp-dependent Protein Kinase a Andmentioning
confidence: 93%
“…One pathway that potentiates presynaptic secretion acts through protein kinase C (PKC, see Tanaka, 1984;Nichols et al,, 1987;Shu and Selmanoff, 1988;Shuntoh et al, 1988; see also Fig. 3).…”
Section: The Impact Of Presynaptic Receptor Activation On the Stimulumentioning
confidence: 99%